CooB plays a chaperone-like role for the proteins involved in formation of CS1 pili of enterotoxigenic Escherichia coli - Voegele, Karl (The National Academy of Sciences of the USA, 1997)
CS1 pili serve as the prototype of a class of filamentous appendages found on the surface of strains of enterotoxigenic Escherichia coli. The four genes needed to synthesize functional CS1 pili in E. coli K12 are: cooA, which encodes the major pilin protein; cooD, which encodes a minor pilin protein found at the tip of the structure; cooC, which encodes a protein found in the outer membrane of piliated bacteria; and cooB. We show here that CooB, which is required for pilus assembly but is not part of the final structure, stabilizes CooA, CooC, and CooD. We previously reported that CooB is complexed with CooA in the periplasm and show here that CooB also is found complexed with CooD in the periplasm. CooB is associated with the membrane fraction only in the presence of CooC, suggesting that these two proteins also interact. This suggests that although it has no homology to known chaperone proteins, CooB serves a chaperone-like role for assembly of CS1.